Functional and structural changes throughout the auditory system following congenital and early-onset deafness: implications for hearing restoration - Butler, Blake E.; Lomber, Stephen G. (Frontiers in Systems Neuroscience, 2013)
The absence of auditory input, particularly during development, causes widespread changes in the structure and function of the auditory system, extending from peripheral structures into auditory cortex. In humans, the consequences of these changes are far-reaching and often include detriments to language acquisition, and associated psychosocial issues. Much of what is currently known about the nature of deafness-related changes to auditory structures comes from studies of congenitally deaf or early-deafened animal models. Fortunately, the mammalian auditory system shows a high degree of preservation among species, allowing for generalization from these models to the human auditory system. This review begins with a comparison of common methods used to obtain deaf animal models, highlighting the specific advantages and anatomical consequences of each. Some consideration is also given to the effectiveness of methods used to measure hearing loss during and following deafening procedures. The structural and functional consequences of congenital and early-onset deafness have been examined across a variety of mammals. This review attempts to summarize these changes, which often involve alteration of hair cells and supporting cells in the cochleae, and anatomical and physiological changes that extend through subcortical structures and into cortex. The nature of these changes is discussed, and the impacts to neural processing are addressed. Finally, long-term changes in cortical structures are discussed, with a focus on the presence or absence of cross-modal plasticity. In addition to being of interest to our understanding of multisensory processing, these changes also have important implications for the use of assistive devices such as cochlear implants.